Growth and development of civil service and bureaucracy in Bangladesh: An overview - Mollah, Md. Awal Hossain (2011)
The aim of this article is to analyse the growth and development of bureaucracy as an institution of government in Bangladesh from historical and politico- administrative perspectives. Although it is now an independent state, various Hindu kings, Muslim emperors, British lords and zamindars of the Indian subcontinent ruled the area of Bangladesh for several hundred years. In 1947, when India and Pakistan emerged as independent states, Bangladesh was a part of Pakistan. To understand the growth and development of bureaucracy in Bangladesh, the article is divided into two broad sections: the colonial legacy of both British India and Pakistan (1601-1971) and the Bangladesh period (1971-2008). The structure and working patterns of bureaucracy in Bangladesh are a legacy of British colonial rule, which impeded reform efforts after Independence and caused politicisation of the administration and governance. Civil-military elitisms reduced accountability of the administration, resulting in a dominating bureaucratic structure with corruption. - Reproduced.
Keywords: Bureaucracy - Bangladesh; Civil service - Bangladesh; Civil service